The Implementation of Antenatal Care with Telehealth Towards Pregnant Women’s Mental Health - Angelia Friksa Tendean; Arlina Dewi; Anggit Wirasto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
Mental health problems among pregnant women must be prevented or managed to prevent more various possible complications that can occur to both mother and fetus, which can be carried out together with Antenatal Care (ANC). Telehealth is a technology-based approach to improving maternal health care. This study aims to discuss the implementation of ANC with telehealth towards pregnant women’s mental health. This study is a literature review conducted by searching databases of PubMed, Proquest, Cochrane Review, and EBSCOhost databases from 2000-2020. The result showed the mode of telehealth had been used varies in nine articles have reviewed, with the most participants were using handphones 56% and computers 11%, and both combination 22%, while application-based 45%, websites 22%, software 11%, internet 11%, and SMS 11%. Implementing telehealth with ANC made it possible to effectively detect early mental health and manage the problem. The result has also shown that telehealth has achieved a good satisfaction level. The common factors that influence telehealth's efficacy include income, education, the age of pregnant women, and gestational age. It can be concluded that telehealth with ANC can effectively improve mental health among pregnant women and be recommended for use by health care providers in pandemic COVID-19.